Synthesis and Crystal Structure Characterization of Oxysilicate Apatites for Stabilization of Sr and Rare‐Earth Elements. Issue 5 (7th February 2016) - Wang, Jingxian; Wei, Fengxia; Lim, Soo Min; Liu, Erjia; Guet, Claude; White, Tim; Dong, ZhiLi
Abstract : Strontium (Sr) containing rare‐earth oxysilicate apatite A I 4 A II 6 (SiO4 )6 O2 is considered a good matrix to accommodate radionuclide as its cation sites can incorporate lanthanide elements other than Sr. Here, we report a study on the synthesis of Nd8 Sr2 (SiO4 )6 O2 and Yb8 Sr2 (SiO4 )6 O2, which adopt P 63 / m apatite symmetry, as well as the characterization of crystallographic structures using X‐ray diffraction and electron microscopy. It is found that A I position is shared by Nd, Yb and Sr, and A I O6 polyhedra are face‐connected, forming column structures, which are linked to SiO4 tetrahedra, creating continuous channels. The Rietveld refinement shows that Nd and Yb prefer the A II position in the channel. The twisted angle of adjacent triangle faces in an A I ‐O polyhedron along [001] is a critical parameter to identify the channel volume and its value varies when different cations are incorporated. The twisted angles for Nd‐apatite and Yb are 24.2° and 22.7° The findings provide a new insight into nuclear waste stabilization by apatite‐type structure.